RADEC AND READING COMPREHENSION: A QUASI-EXPERIMENTAL STUDY IN ELEMENTARY SCHOOL EDUCATION - Syahrizal, Irvan; Adi, Banu Setyo; Firdaus, Fery Muhamad; Calik, Muammer (PD PGMI se Indonesia, 2025)
This study seeks to explore the impact of the RADEC education model on the reading comprehension abilities of fourth-grade students. This study adopts a quasi-experimental design involving pre-test and post-test measurements on unequal control groups. The research population consists of all fourth-grade students at SDN Sokowoten Baru and the sample was selected purposive sampling with a total of 50 students, 25 participants from the experimental and control groups. The data collection process involved the use of tests and data analysis using descriptive statistics and assumption tests. The normality test results showed that all groups had a significance value ? 0.05, indicating that the data distribution was normal. Furthermore, Levene's test for homogeneity showed a significance value of 0.876 > 0.05, meaning that the data was homogeneous. Analysis of the post-test results showed a Sig. of 0.000, so Ha is accepted. This indicates that the increase in post-test results in the RADEC group is significantly higher than in the Direct Instruction. Thus, the RADEC learning model contributes positively to students' reading comprehension skills. Theoretically, these findings support the constructivist learning approach and the development of reading strategies based on higher-order thinking skills. Practically, the RADEC model helps teachers create more interactive, structured, and meaningful reading learning experiences at the primary school level.